2018
DOI: 10.1002/ijop.12492
|View full text |Cite
|
Sign up to set email alerts
|

Rational beliefs, happiness and optimism: An empirical assessment of REBT's model of psychological health

Abstract: This study sought to test the validity of the psychological health model of Rational Emotive Behaviour Therapy (REBT). Specifically, this study sought to investigate if rational beliefs were associated with happiness and optimism. A multinational sample of 397 university students completed self-report measures of rational beliefs, happiness and optimism. Structural equation modelling (SEM) was used in order to test the validity of the REBT model of psychological health. The result of the SEM analysis provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…These results may point out that REBT can also be used in supporting positive psychology in clients. The result is consistent with findings that REBT not only alleviates psychological distress but also builds positive emotions (Oltean et al, 2019). However, an interesting result was that OWB-hope scores, a variable representing one of the positive aspects of mental health, did not improve by REBT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results may point out that REBT can also be used in supporting positive psychology in clients. The result is consistent with findings that REBT not only alleviates psychological distress but also builds positive emotions (Oltean et al, 2019). However, an interesting result was that OWB-hope scores, a variable representing one of the positive aspects of mental health, did not improve by REBT.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are inconsistent with the Sealid and Nordahl (2017) study, which found that the ABC Model effectively reduces anxiety symptoms while increasing feelings of hope. REBT's ABCDEF may extend to the model of to ABCDEFG (Artiran, 2019a;Dryden, 2019) in order to add some positive interventions (Oltean, et al, 2019;Sapancı & Bahtiyar, 2018;Whitfield, 2006). This study focuses on culturally specific, positive goals of a Turkish population (Artiran, 2019a) due to the practitionaire's style of applying REBT, but more such relevant studies are needed to investigate the validity of such model.…”
Section: Discussionmentioning
confidence: 99%
“…However, research does indicate that irrational beliefs are important cognitive variables in post-traumatic stress (PTS) symptoms, while only rational acceptance beliefs seem to have a protective role in the emergence of PTS symptoms (Hyland et al, 2014). Another explanation of why the RaBel model did not predict psychopathology is that rational beliefs are more likely to be associated with positive well-being variables such as happiness and optimism (Oltean et al, 2018), rather than ill-being variables.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rather than REBT being seen as a remedial approach to irrationality and human misery, it can be more accurately considered to be a positive approach to helping people to apply rationality to life. Indeed, it is recognised that REBT and the rationality it presents can help people live pleasurable and fulfilled lives, and can be aligned with positive psychology (Bernard et al, 2010;Oltean et al, 2019).…”
Section: The Development Of Rebt Interventions In the Sport Fieldmentioning
confidence: 99%